Dose-dense cisplatin with gemcitabine for relapsed platinum-resistant ovarian cancer. Issue 2 (February 2019) - Morgan, Robert D; Clamp, Andrew R; Zhou, Cong; Saunders, Geoff; Mescallado, Nerissa; Welch, Richard; Mitchell, Claire; Hasan, Jurjees; Jayson, Gordon C
Abstract : Introduction: Standard of care treatment for women who develop relapsed ovarian cancer includes sequential platinum- and/or paclitaxel-based chemotherapy, with reducing disease-free intervals. Once platinum resistance develops, treatment options become limited and dose-dense regimens may be offered. We report the efficacy and safety of dose-dense cisplatin with gemcitabine chemotherapy for relapsed platinum-resistant ovarian cancer. Methods: A retrospective analysis of all patients with relapsed, platinum-resistant ovarian, primary peritoneal or fallopian tube cancer treated with cisplatin 35 mg/m 2 of body surface area by intravenous infusion with gemcitabine 1000 mg/m 2 of body surface area by intravenous infusion on days 1 and 8 of every 21-day treatment cycle between 1 January 2009 and 1 June 2017. Results: Ninety-four eligible patients had received a median of three (range one–eight) prior lines of cytotoxic therapy for relapsed ovarian cancer. Sixty patients (64%) had received ≥ 1 prior dose-dense chemotherapy regimen. Dose-dense cisplatin with gemcitabine was associated with a median progression-free survival (PFS) of 4.4 months (95% CI 3.6 to 5.3) and overall survival of 7.6 months (95% CI 5.6 to 9.6). The median PFS for dose-dense cisplatin with gemcitabine as first- (n = 34), second- (n = 42), and third-line or later (n = 18) dose-dense therapy was 4.2 (95% CI 3.2 to 5.2), 5.0 (95% CI 3.5 to 6.5), and 4.2 (95% CI 3.3 to 5.1) months respectively. The RECIST objective response rate for first-, second-, and third-line dose-dense cisplatin with gemcitabine was 23%, 14 %, and 7 % respectively. The most common grade 3 – 4 adverse events were thrombocytopenia (20%), anemia (18%), and neutropenia (14%). Discussion: Dose-dense cisplatin with gemcitabine provides modest efficacy whether it is used as a first- or subsequent line of dose-dense chemotherapy to treat relapsed platinum-resistant ovarian cancer and the toxicity is manageable with supportive measures.